'Feeling fat' amid the COVID-19 pandemic: Examining the role of emotion dysregulation in the body displacement hypothesis. (January 2022) - Mehak, Adrienne; Miller, Alexia E.; Trolio, Vittoria; Racine, Sarah E.
Abstract: 'Feeling fat, ' the somatic experience of being overweight not entirely explained by objective weight, may occur due to the projection of negative affect onto the body. Individuals may manage 'feeling fat' via eating pathology (e.g., binge eating or dietary restriction) rather than address the source of negative affect. Thus, 'feeling fat' may occur in the absence of adaptive emotion regulation strategies. The COVID-19 pandemic has increased negative affect widely and may potentially contribute to the experience of 'feeling fat' and eating pathology among individuals with emotion dysregulation. This study examined whether emotion dysregulation moderates 'feeling fat's' role as a mechanism underlying the relationship between COVID-19-related distress and eating pathology. This uniqueness of this model to eating pathology was investigated by comparing effects for binge eating and dietary restriction versus anxiety, depression, and problematic alcohol use. Structural equation modelling was used to analyze questionnaire data from 877 participants (77.3% women). 'Feeling fat' explained significant variance in the relationship between COVID-19-related distress and both binge eating and restriction. Emotion dysregulation modulated the strength of these relationships. However, 'feeling fat's role in the relationship between pandemic-related distress and negative psychological outcomes was not unique to eating pathology and did not vary based upon emotion dysregulation. Individuals with elevated emotion dysregulation are more likely to report eating pathology, but not other outcomes, in the context of 'feeling fat'. In contrast, 'feeling fat' underlies the relationship between COVID-19-distress and transdiagnostic psychological outcomes, meaning 'feeling fat' should be considered in risk for psychopathology beyond eating disorders. Highlights: COVID-19-related distress correlates with 'feeling fat' and eating pathology. Feeling fat strengthens the relation between COVID-19 distress and eating pathology. Feeling fat links pandemic-related distress and eating pathology. Feeling fat links COVID-19 distress and clinical outcomes beyond eating pathology. Feeling fat may, in part, signify unresolved negative affect projected on the body.